PENGARUH SOCIAL MEDIA INFLUENCER DAN BRAND IMAGE TERHADAP BRAND TRUST DAN KEPUTUSAN PEMBELIAN PRODUK SCARLETT WHITENING (Studi Pada Generasi Z Kota Pekanbaru) - Putri Irvania Yurike; Nursanti Aida; Wasnury Rendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine how the influence of Social Media Influencers andBrand Image on Purchase DecisionsforScarlett Whitening Products with Brand Trustas anIntervening Variable in Generation Z Pekanbaru City, either partially orsimultaneously.The population in this study were users of Scarlett Whitening productsin Pekanbaru City.The sampling technique used the lameshow formula with a total sample of 100 people. Thedata collection technique used a questionnaire in which theresearch method used was aquantitative method, this study used primary data with a path analysis model. The findingsof this study obtained the influence of social media influencers on brand trust andpurchasing decisions and the influence of brand image on brand trustand purchasingdecisions, while brand trust had an effect on purchasing decisions forscarlett whiteningproducts. For indirect effects, it was found that there was an influence of social mediainfluencers on purchasing decisions through brand trust, andalso the influence of brandimage on purchasing decisions through brand trust. Key Words: Social Media Influencer, Brand image, Brand Trust, PurchasingDecisions